Prognostic effect of the preoperative albumin-to-globulin ratio bladder cancer: a meta-analysis - Fangfang Huang; Changyun Chen; Yan Mao; Tingting Lin; Qianqian Hu (Frontiers in Medicine, 2026)
Background The preoperative albumin-to-globulin ratio (AGR) has emerged as a potential prognostic indicator in various malignancies. However, its specific prognostic value in bladder cancer remains to be fully elucidated. Thus, the association between preoperative the AGR and the prognosis of bladder cancer should be systematically evaluated through a meta-analysis of the available evidence. Methods A systematic search was performed across major electronic databases (PubMed, Embase, and the Cochrane Library) to identify studies reporting the prognostic significance of AGR in bladder cancer. The primary outcomes were overall survival (OS) and progression-free survival (PFS). Hazard ratios (HRs) and 95% confidence intervals (CIs) were pooled to assess the strength of the association. Results A total of 8 studies involving 8305 patients were included in this meta-analysis. Our pooled results found that a low preoperative AGR was significantly associated with poor CSS (HR = 1.25, 95% CI: 1.11–1.38), PFS (HR = 1.92, 95% CI: 1.35–2.50), RFS (HR = 1.36, 95% CI: 1.09–1.64) compared with a high AGR in patients with bladder cancer. Conclusion The preoperative AGR is a reliable prognostic factor for bladder cancer, suggesting that it could be integrated into clinical practice for risk assessment.